2013
DOI: 10.1111/ctr.12244
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation: what else can be done besides legislature?

Abstract: With the ongoing organ shortage for transplantation, Singapore has adopted an organ opt-out scheme: Human Organ Transplant Act (HOTA) that presumes consent unless specified otherwise. Likewise, receptivity of doctors and medical students (MS), as future doctors, can positively influence organ donation (OD) rates. We explored the knowledge and attitudes of MS toward OD. MS from all five yr of medical school were recruited using self-administered questionnaires. There were 294 completed questionnaires with 49.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The level of support for the change in legislation observed in NHS staff respondents in this study is also reassuring, they are higher than levels of support identified in other international studies where there is opt-out legislation [ 13 , 22 ]. It is comparable to Scotland where prior to the planned change to opt-out it was reported that staff felt it would have a positive impact [ 23 ].…”
Section: Discussionsupporting
confidence: 42%
“…The level of support for the change in legislation observed in NHS staff respondents in this study is also reassuring, they are higher than levels of support identified in other international studies where there is opt-out legislation [ 13 , 22 ]. It is comparable to Scotland where prior to the planned change to opt-out it was reported that staff felt it would have a positive impact [ 23 ].…”
Section: Discussionsupporting
confidence: 42%
“…Educational policies aimed at decreasing family refusal are essential because most transplants in Brazil come from deceased donors and, by law, donations rely on family consent. As constantly advocated in the literature, education is a fundamental tool for increasing the individual autonomy for making conscious decisions, improving awareness, building a generally positive attitude regarding ODT, and aiding choices about organ donation …”
Section: Overview Of the Brazilian Health Care System And Its Organ Tmentioning
confidence: 99%
“…It is worth noting that a family's decision about organ donation occurs while they are mourning the loss of a loved one, often without previous thought on the matter . Other aggravating factors are dissatisfaction with the care received by the patient, the distrust of the National Transplant System organ allocation system, and the unfamiliarity with the concept of brain death, frequently resulting in insecurity about the diagnosis of death and the irreversibility of this clinical status . The doubts prevail when the health team fails to apply the technical knowledge and interpersonal abilities required to provide informed support and create an empathetic connection with the family during the organ donation interview …”
Section: Overview Of the Brazilian Health Care System And Its Organ Tmentioning
confidence: 99%
“…Unlike the American and European societies, who are generally more open to donation, our society comprising predominantly of Chinese and Malay societies have traditional cultural values, which result in greater antipathy towards organ/tissue donation. 9 This was evident in various studies, for instance, 27% of 2930 Chinese participants would not consent to donate their own organs after their passing due to the traditional Chinese belief of the necessity to have an intact body after death for a good afterlife. 10,11 Another evidence of traditional cultural values influencing people's decision to donate tissue/organs is the statistics obtained from 2000 to 2010 by National Transplant Resource Centre, Kuala Lumpur, which reported that donation among the Malay community (the dominant ethnic group in Malaysia) contributed to only 6.36% of the total organ donation as compared to 61.86% by Chinese and 31.78% by Indians; the study cited the Malay community's perception that their religion, Islam, did not permit them to donate tissue/organs as the primary reason for their low donation rates.…”
Section: Discussionmentioning
confidence: 99%